2020
DOI: 10.3390/horticulturae6010009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydraulic Loading Rate on Spatial and Temporal Water Quality Characteristics and Crop Growth and Yield in Aquaponic Systems

Abstract: Aquaponics is a rapidly growing food-production system integrating aquaculture and hydroponic crop production through an energy-intensive water recirculation process. Crop performance and yield in aquaponics are affected by essential and toxic nutrient levels in the root zone, which can be regulated by water flow rate. This study was conducted to examine the effects of hydraulic loading rate (HLR) on water quality and crop growth and yield in recirculating aquaponic systems set at three different loading rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 64 publications
5
30
0
Order By: Relevance
“…Nutrient requirements for optimal growth of plants varies by species, growth stage, temperature, pH, and other environmental factors (Hawkesford et al, 2011;Abbasi et al, 2017;Prieto et al, 2017). The yield of all three plant species increased significantly (p < 0.05) with each harvest (Figure 2), which was similar to the result published by Yang and Kim (2020b). They suggested the increased production was related to the maturity of the system.…”
Section: Plantssupporting
confidence: 84%
“…Nutrient requirements for optimal growth of plants varies by species, growth stage, temperature, pH, and other environmental factors (Hawkesford et al, 2011;Abbasi et al, 2017;Prieto et al, 2017). The yield of all three plant species increased significantly (p < 0.05) with each harvest (Figure 2), which was similar to the result published by Yang and Kim (2020b). They suggested the increased production was related to the maturity of the system.…”
Section: Plantssupporting
confidence: 84%
“…The water temperature in aquaponic systems was higher than those in hydroponics. Lettuce is a cool-season crop, of which growth can be affected by air or root zone temperature [40], and, therefore, the higher water temperatures in aquaponic systems may be one of the causes of the reduced plant growth.…”
Section: Growth and Yield Of Plant And Fish Cropsmentioning
confidence: 99%
“…Although HLR dictates optimum contact time for nutrient and microbe interaction with plant roots (Wongkiew et al 2017), very few studies have reported on the effects of HLR on microbial ecology and diversity in aquaponics. The major focus has been on optimising HLR for water quality, as well as plant and fish growth and health (Endut et al 2010;Shete et al 2016;Yang and Kim 2020). Endut et al (2010) compared five HLRs ranging between 0.64 and 3.20 m day −1 and reported an optimal HLR for fish production, plant growth, and nutrient removal of 1.28 m day −1 .…”
Section: Hydraulic Loading Ratementioning
confidence: 99%